Characteristicsof Liquid Smoke of Tabah Bamboo Stem (Gigantochloa nigrociliataBUSE-KURZ) on Distillation Results at Different Temperatures - Swandewi, Kadek Rahayu; Kencana, Pande Ketut Diah; Yulianti, Ni Luh (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
The purpose of this study were to determine the density, yield, and chemical compounds (pH, total acid, and total phenol) contained in liquid smoke distillates as a pyrolysis result of tabah bamboo stems at temperatures of 125oC and 150oC. Furthermore, this study used a Completely Randomized Design (CRD) with a single factor that is using temperature (125oC and 150oC). Analysis of variance showed that the difference between 125oC and 150oC temperatures had a significant effect on the analysis result of tabah bamboo pyrolysis liquid smoke distillation. The results were the highest density of 35.8575g at 125oC and the lowest was 31.629g at 150oC, the highest pH was 3.20 at 125oC and the lowest was 3.14 at 150oC, the highest total acid was 10.94% at 150oC and the lowest 7.70% at 125oC, the highest total phenol was 0.65% at temperature of 150oC and the lowest was 0.61% at 125oC. The smallest real difference analysis showedthat temperature of 125oC and 150oC significantly affected pH, total acid, and total phenol. The resultsshowed differences in the characteristics of liquid smoke before and after distillation